Chemistry of Guanidinate‐Stabilised Diboranes: Transition‐Metal‐Catalysed Dehydrocoupling and Hydride Abstraction. Issue 39 (28th August 2014) - Wagner, Arne; Litters, Sebastian; Elias, Jana; Kaifer, Elisabeth; Himmel, Hans‐Jörg
Abstract Herein, we analyse the catalytic boron–boron dehydrocoupling reaction that leads from the base‐stabilised diborane(6) [H2B(hpp)]2 (hpp=1, 3, 4, 6, 7, 8‐hexahydro‐2H‐pyrimido[1, 2‐a]pyrimidinate) to the base‐stabilised diborane(4) [H2B(hpp)]2. A number of potential transition‐metal precatalysts was studied, including transition‐metal complexes of the product diborane(4). The synthesis and structural characterisation of two further examples of such complexes is presented. The best results for the dehydrocoupling reactions were obtained with precatalysts of Group 9 metals in the oxidation state of +I. The active catalyst is formed in situ through a multistep process that involves reduction of the precatalyst by the substrate [H2B(hpp)]2, and mechanistic investigations indicate that both heterogeneous and (slower) homogeneous reaction pathways play a role in the dehydrocoupling reaction. In addition, hydride abstraction from [H2B(hpp)]2 and related diboranes is analysed and the possibility for subsequent deprotonation is discussed by probing the protic character of the cationic boron–hydrogen compounds with NMR spectroscopic analysis.